A Study on Global Path Planners Algorithms for the Simulated TurtleBot 3 Robot in ROS - Brasil, Pedro; Pereira, Fabio; Cuadros, Marco Antonio; Cukla, Anselmo Rafael; Gamarra, Daniel Fernando (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This article aims to study global path planners algorithms using a mobile robot in the ROS (Robot Operating System) framework. Experiments were carried out in different environments, aiming to apply the Dijkstra and A* algorithms in simulation. The tests were performed with the robot TurtleBot 3 Burger, which runs using open source software. Location and orientation data from the sensors of the robot were stored. After analyzing the results, there was a slight superiority of Dijkstra algorithm from the ROS libraries, in relation to the A* algorithm in the environments with obstacles.